PENGOLAHAN LIMBAH CAIR BATIK MENGGUNAKAN TEKNOLOGI MEMBRAN NANOFILTRASI DI KOTA PEKALONGAN - Kiswanto, Kiswanto; Rahayu, Laila Nur; Wintah, Wintah (BAPPEDA Kota Pekalongan, 2019)
Pekalongan is the most famous batik city in Indonesia. UNESCO was crowned Pekalongan as the most creative batik city. Along with the coronation of Batik city, emerging problems related to the pollution of waste batik that ultimately damage the environment. It needs to be done fast and environmentally friendly batik waste processing. One alternative is the processing of batik waste using membrane technology. To know the performance of membrane nanofiltration in color allowance, COD, BOD, TSS, and metal Pb used batik liquid waste with different concentrations. This research was conducted to analyse the influence of pressure (4, 5, and 6 bar) against flux and the degree of windection of each of the parameters. The optimum pressure of membrane nanofiltration for all parameters is 6 bar. The results showed that the results of the rejection of colorants, COD, BOD, TSS and Pb respectively without dilution, 10 times dilution, 20 times dilution, 30 times in successive dilution is (98,29%-99.87%), (92,10-100%), (100%), (99,25-100%), ( 95,25-100%). The results showed that the color allowance, COD, BOD, TSS and Pb Metal had fulfilled the quality standards for the optimum pressure of 6 bar according to Ministry of Environment Regulation No. 5 year 2004 and Local Regulations of Central Java No. 5 year 2012. Potential of membrane nanofiltration technology can be used for the processing of batik liquid waste. Keywords: Batik Waste, Nanofiltration, Pressur, Color